Granulomatosis polyangiitis: an otorhinolaryngological perspective - Hedge, Jyotirmay Shyamsundar; Dechamma, Shruthi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Granulomatosis with polyangiitis or Wegeners granulomatosis is a rare entity, however is known to have specific otorhinolaryngological manifestations. Initial clinical manifestations could be subtle but deteriorate rapidly with an underlying active autoimmune process which can be life threatening in severe subglottic stenosis. We report a case of Granulomatosis with polyangiitis in an adolescent girl initially presented with otitis media refractory to treatment and epistaxis and rhinitis and eventually with the progression of disease presented with subglottic stenosis. Diagnosis was made by anti-neutrophil cytoplasmic antibody proteinase 3 (ANCA-PR3) positive status and histological confirmation by nasal biopsy, elevated C-reactive protein (CRP) levels and renal involvement with evidence of microalbuminuria. She underwent dilatation of the subglottic stenosis twice, with resection of the stenotic mass by coblation. The diagnostic and therapeutic challenges faced are emphasized in this report.